Dynamic Analysis of Retailers’ Paid Membership Strategy - Lina Xu; Zhiqing Meng (Discrete Dynamics in Nature and Society)
Paid membership system has attracted more and more attention from retailers because of its advantages in improving customer loyalty, increasing repeat purchases and corporate cash flow in the short term, and collecting consumption data conveniently. In the fierce competition environment, it is an interesting topic whether the paid membership card can be accepted by the customers as soon as possible. Based on the theory of evolutionary game, this paper discusses the strategies of retailers to implement the paid membership in the case of two different consumer groups. The results show that only when the relationship between the parameters meets certain conditions can the paid membership card be accepted smoothly. In order to satisfy the condition, retailers should take such measures: making the difference between service level and membership card price bigger and reducing consumers’ estimated default risk and retailers’ service adjustment factor. The results of this study provide a useful reference for retailers to successfully implement the paid membership system.